Active Vibration Control of a Microactuator for the Hard Disk Drive Using Self-Sensing Actuation. (5th March 2012) - Sasaki, Minoru; Inoue, Yoshihiro; Yamada, Hiroyuki
Abstract : This paper presents the self-sensing control of a microactuator for hard disk drives. The microactuator uses a PZT actuator pair installed on the suspension assembly. The self-sensing microactuator forms a combined sensing and actuation mechanism. Direct velocity feedback and positive position feedback are used in this paper. Our experimental results show that both strategies are effective in suppressing vibrational modes and successfully demonstrate the feasibility of using a self-sensing actuator on an HDD suspension assembly.